Data analysis on innovation in Greece. The challenge of surveying innovation in enterprises and economy - Chrysomallidis, Charalampos (The Greek Review of Social Research, 2017)
Innovation, as a meaning, is often used in a dilating way, while surveys at national level to measure innovation in enterprises are subject to specific criteria, limiting their analytical and explanatory power. The article aims to initially show off the problems with the concept of innovation, taking into account recent developments. Then it presents factually innovation in Greece, highlighting the –sometimes contradictory- conclusions that arise from official and other reviews on innovation. Finally the article attempts to interpret the reasons for this phenomenon, focusing on the Greek case.